Utilização da cinza do bagaço de cana-de-açúcar (CBC) em substituição parcial ao agregado miúdo em concreto não estrutural - Nascimento, Maria da Conceição Aguiar do (2016)
Brazil is the world's largest non-sugar-alcohol complex that has been expanding in recent times, driven by the advent of bioenergy, exerting a leadership in all segments. The residue generated at the end of the sugarcane bagasse milling process is used for the generation of energy by burning in boilers. At the end of the burning as residual ash are released into the environment inadequately, and may cause environmental problems due to the generation of waste as a sugarcane bagasse ash. The interest of the research is to justify the demand through a job offer from the sugarcane bagasse ash (CBC) in concrete structures, due to the large volume of generation and the concern with the environment. The objective of this research is to evaluate the performance of the conventional contract made of sugar cane residues proved from mills. The results were reported with a 0%, 20% and 40% substitution of natural sand by BCC, where this mixture may contribute to a compound more difficult than conventional concrete. It is also concluded that although the use of CBC has not significantly reduced the final value of m³ of concrete, the gain in relation to the mechanical performance was higher. It can be concluded that the specimens produced have obtained sufficient mechanical strength to be dismantled, transported and conditioned prior to use, in the same way as the referents.